User Experience Design on Visualization of Mobile-Based Land Monitoring System Using a User-Centered Design Approach - Setiyawati, Nina; Dwi Purnomo, Hindriyanto; Mailoa, Evangs (International Journal of Interactive Mobile Technologies (iJIM), 2022)
The use of information and communication technology could increase the quantity and quality of agricultural production, including horticulture. This study focuses on the development of a mobile-based interface that makes it easier for farmers to view the data obtained from the results of land monitoring. In designing mobile devices, applications, and user interfaces, it is important to consider the user experience. This paper focuses on UX design which is which is based on User-Centered Design approach that focuses on user needs and prioritizes empathy for users, so as to accommodate the identification of user needs and produce high fidelity pro-totypes. Based on the System Usability Scale and the User Experience Questionnaire testing on the prototype, it was found that the level of acceptance of horticultural farmers was positive with the level of the value of all UX elements above the average